2017
DOI: 10.3892/mmr.2017.7578
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin inhibits cancer growth and metastasis via activation of EIF2AK2

Abstract: Kisspeptin is a protein encoded by the KISS1 gene, which has been reported to suppress the metastatic capabilities of various types of cancer cells, through the activation of its G‑protein coupled receptor GPR54. However, the molecular mechanisms underlying the involvement of kisspeptin‑mediated signaling in the inhibition of cancer cell migration and invasion have yet to be elucidated. The present in vitro cell proliferation, migration and invasion assays and in vivo experimental metastasis studies demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…They were able to detect an inhibition of cell migration and invasion, as well as re-sensitization of cells to chemotherapeutics when KISS1 was re-expressed in PC3M cells that lack KISS1 (23). Similar results with inhibition of prostate cancer cell growth and metastasis have been demonstrated in a recent study by activation of eukaryotic translation initiation factor 2a kinase 2 (EIF2AK2) upon kisspeptin and KISS1R stimulation (64).…”
Section: Strong Kiss-r Immunohistochemical Expression (Ie) In Normasupporting
confidence: 70%
“…They were able to detect an inhibition of cell migration and invasion, as well as re-sensitization of cells to chemotherapeutics when KISS1 was re-expressed in PC3M cells that lack KISS1 (23). Similar results with inhibition of prostate cancer cell growth and metastasis have been demonstrated in a recent study by activation of eukaryotic translation initiation factor 2a kinase 2 (EIF2AK2) upon kisspeptin and KISS1R stimulation (64).…”
Section: Strong Kiss-r Immunohistochemical Expression (Ie) In Normasupporting
confidence: 70%
“…To understand how kisspeptin might exert direct anti-metastatic effects in prostate cancer, KISS1 was re-expressed in PC3M cells that lack KISS1 and this resulted in an inhibition of cell migration and invasion and re-sensitization of cells to chemotherapeutics ( 10 ). Another study showed that KISS1R signaling induced the activation of eukaryotic translation initiation factor 2α kinase 2 (EIF2AK2) in prostate cancers and thereby inhibited cell growth and metastasis ( 69 ). Clearly, kisspeptin can act on prostate cancer cells both indirectly via the HPG axis and directly, thus its clinical value in treating prostate cancer is very promising and awaits further studies.…”
Section: Metastasis Suppressor Rolesmentioning
confidence: 99%
“…For example, the upregulation of Sox2 in breast cancer tissues was associated with lymph node metastasis, pathological grade and TNM classification (6). Kisspeptin suppressed cancer growth and metastasis by activating EIF2AK2 in CRC (7). Cyclin D2/miR-1297 signaling was associated with the growth and metastasis of CRC (8).…”
Section: Introductionmentioning
confidence: 99%